Coordination in Games with Strategic Complementarities: An Experiment on Fixed vs. Random Matching. (22nd October 2012) - Hyndman, Kyle; Kraiselburd, Santiago; Watson, Noel
<x xml:space="preserve">Abstract</x> In this article, we study behavior in a series of two‐player supply chain game experiments. Each player simultaneously chooses a capacity before demand is realized, and sales are given by the minimum of realized demand and chosen capacities. We focus on the differences in behavior under fixed pairs and random rematching. Intuition suggests that long‐run relations should lead to more profitable outcomes. However, our results go against this intuition. While subjects' capacity choices are better aligned (i.e., closer together) under fixed pairs, average profits are more variable. Moreover, learning is slower under fixed pairs—so much so that over the last five periods, average profits are actually higher under random rematching. The underlying cause for this finding appears to be a "first‐impressions" bias, present only under fixed matching, in which the greater the misalignment in initial choices, the lower are average profits.